Sensory spinal interoceptive pathways and energy balance regulation - Heike Münzberg; Hans-Rudolf Berthoud; Winfried L. Neuhuber (Elsevier, 2023)
Interoception plays an important role in homeostatic regulation of energy intake and metabolism. Major interoceptive pathways include gut-to-brain and adipose tissue-to brain signaling via vagal sensory nerves and hormones, such as leptin. However, signaling via spinal sensory neurons is rapidly emerging as an additional important signaling pathway. Here we provide an in-depth review of the known anatomy and functions of spinal sensory pathways and discuss potential mechanisms relevant for energy balance homeostasis in health and disease. Because sensory innervation by dorsal root ganglia (DRG) neurons goes far beyond vagally innervated viscera and includes adipose tissue, skeletal muscle, and skin, it is in a position to provide much more complete metabolic information to the brain. Molecular and anatomical identification of function specific DRG neurons will be important steps in designing pharmacological and neuromodulation approaches to affect energy balance regulation in disease states such as obesity, diabetes, and cancer.